Classical Allusions at Memorial Post-Mortem Photography of the 19th and Early 20th Century: The Ancient Greek Motif of ‘Hypnos and Thanatos’ - Stamatopoulou, Myrto (Pnyx: Journal of Classical Studies, 2025)
Photography and archeology share the common feature of connecting the present to the past, yet following reverse processes. Photography captures the present transforming it immediately into past, as opposed to archeology which discovers the past and brings it back to the present. The present article focuses on the reception of the eternal sleep’s pattern in the memorial postmortem photography. This particular ancient Greek motif bears its roots in the mythological deities of Hypnos and Thanatos and conveys the perception that the deceased is not dead, but merely asleep. There can be no other means than the archeological findings (amphorae and sculptures) and the literary sources as testimonies to the inseparable collaboration between these two twin deities for the transition of the dead from this earthly world to the ethereal world of the souls. The visualization of the eternal sleep’s pattern is very often observed in the memorial postmortem representations, especially in the 19th century and the early 20th century. When photography firstly appeared, bearing a quite unpopular technique, people had no other photographic representation of themselves as alive and the mourning portrait was their only opportunity to depict their physical characteristics. Sleep as a simulation of death offered the necessary illusion that the beloved dead is asleep, thus suggesting a manifestation of life.Photography establishes, by definition, a dynamic relationship between the present and the past as it captures ephemeral moments of the present, instantaneously relegating them to the past. This article explores the reception and enduring influence of the “eternal sleep” motif in memorial post-mortem photography of the late nineteenth and early twentieth centuries. Rooted in ancient Greek mythology and specifically associated with the twin deities Hypnos (Sleep) and Thanatos (Death), this iconographic motif conveys the notion that the deceased is not dead but merely asleep. Through this imagery, death is not depicted as an absolute cessation but rather as a liminal state of repose, suggestive of continuity or transition. The visual expression of this motif became especially prominent in post-mortem photographic representations of the period, when many individuals had never been photographed in life, making the mourning portrait their sole visual record. The motif of sleep, as a simulacrum of death, provided mourners with the consolatory illusion that their loved one was merely resting, thereby mitigating the stark finality of death while symbolically asserting life through the still image. Adopting reception theory and the Annales School’s emphasis on the longue durée and collective mentalities, this article argues that the persistence of the “last sleep” motif in 19th-century post-mortem photography reflects long-standing symbolic patterns from ancient Greek art and literature, demonstrating how cultural memory has shaped modern representations of death as a serene and eternal sleep, and consequently as something readily comprehensible to human consciousness.